Influence of physical contact on pacing strategies during game-based activities - Johnston, R. D.; Gabbett, T. J.; Seibold, A. J.; Jenkins, D. G. (International Journal of Sports Physiology and Performance, 2014)
Purpose: Repeated sprinting incorporating tackles leads to greater reductions in sprint performance than repeated sprinting alone. However, the influence of physical contact on the running demands of game-based activities is unknown. The aim of this study was to determine whether the addition of physical contact altered pacing strategies during game-based activities. Methods: Twenty-three elite youth rugby league players were divided into 2 groups. Group 1 played the contact game on day 1 while group 2 played the noncontact game; 72 h later they played the alternate game. Each game consisted of offside touch on a 30 × 70-m field, played over two 8-min halves. Rules were identical between games except the contact game included a 10-s wrestle bout every 50 s. Microtechnology devices were used to analyze player movements. Results: There were greater average reductions during the contact game for distance (25%, 38 m/min, vs 10%, 20 m/min; effect size [ES] = 1.78+/-1.02) and low-speed distance (21%, 24 m/min, vs 0%, 2 m/s; ES = 1.38+/-1.02) compared with the noncontact game. There were similar reductions in high-speed running (41%, 18 m/min, vs 45%, 15 m/min; ES = 0.15+/-0.95). Conclusions: The addition of contact to game-based activities causes players to reduce low-speed activity in an attempt to maintain high-intensity activities. Despite this, players were unable to maintain high-speed running while performing contact efforts. Improving a player`s ability to perform contact efforts while maintaining running performance should be a focus in rugby league training.